A composite microbial agent containing bacterial and fungal species: Optimization of the preparation process, analysis of characteristics, and use in the purification for volatile organic compounds. (October 2016) - Cheng, Zhuowei; Lu, Lichao; Kennes, Christian; Ye, Jiexu; Yu, Jianming; Chen, Dongzhi; Chen, Jianmeng
Graphical abstract: Highlights: A composite microbial agent containing bacterial and fungal species was constructed. The adsorption of carriers could be neglected compared to the micro-biodegradation. The microbial agent was better than the microbial suspension in bioactivity-storage. The microbial agent performed better in continuous degradation and starvation shock. Microbial analysis showed that special strains were not suffered in the construction. Abstract: Proper preservation of microbial activity over long periods poses a considerable challenge for pollutant biopurification. A composite microbial agent, mainly composed of bacteria and fungi isolated by the current research team, was constructed in this study and its performance in the removal of mixed waste gases (containing α-pinene, n-butyl acetate and o-xylene) was investigated. According to the removal efficiency in the first 24 h and the response to starvation, the optimal ratio of selected carriers (activated carbon, wheat bran and sawdust) was found to be 1:2:1. In some cases of storages, the removal capability of the microbial agent was more than twice that of the suspension. Microbial analysis showed that the inoculated bacterial and fungal strains dominated the agent preparation and utilization. These results indicated that the agent has potential for use in biopurification of mixed waste gas, favoring the reduction of environmental passives and longer retention of microbial activity.